Electrically and Magnetically Tunable Valley Polarization in Monolayer MoSe2 Proximitized by a 2D Ferromagnetic Semiconductor. (11th June 2022) - Zhang, Tongyao; Zhao, Siwen; Wang, Anran; Xiong, Zhiren; Liu, Yingjia; Xi, Ming; Li, Songlin; Lei, Hechang; Han, Zheng Vitto; Wang, Fengqiu
Abstract: The emergence of atomically thin valleytronic semiconductors and 2D ferromagnetic materials is opening up new technological avenues for future information storage and processing. A key fundamental challenge is to identify physical knobs that may effectively manipulate the spin‐valley polarization, preferably in the device context. Here, a novel spin functional device that exhibits both electrical and magnetic tunability is fabricated, by contacting a monolayer MoSe2 with a 2D ferromagnetic semiconductor Cr2 Ge2 Te6 . Remarkably, the valley‐polarization of MoSe2 is found to be controlled by a back‐gate voltage with an appreciably enlarged valley splitting rate. At fixed gate voltages, the valley‐polarization exhibits magnetic‐field and temperature dependence that corroborates well with the intrinsic magnetic properties of Cr2 Ge2 Te6, pointing to the impact of magnetic exchange interactions. Due to the interfacial arrangement, the charge‐carrying trion photoemission predominates in the devices, which may be exploited to enable drift‐based spin‐optoelectronic devices. These results provide new insights into valley‐polarization manipulation in transition metal dichalcogenides by means of ferromagnetic semiconductor proximitizing and represent an important step forward in devising field‐controlled 2D magneto‐optoelectronic devices. Abstract : In this paper, by contacting a monolayer MoSe2 with a 2D ferromagnetic semiconductor Cr2 Ge2 Te6, a novel spin‐valley functional device that exhibits both electrical and magnetic tunability is demonstrated. This provides a new physical knob that may effectively manipulate the spin‐valley polarization in the device context.